Pursing Indigenous-Inclusive Curriculum in Social Work Tertiary Education: Feeling my Way as a Non-Indigenous Educator - Gair, Susan (The Australian Journal of Indigenous Education, 2007)
Abstract The retention and completion rates of Indigenous students undertaking tertiary studies continue to be disappointing. The contribution of Eurocentric curricula to such an outcome has been proposed in the Australian and international literature. Remaining very conscious of my status as a white, female, social work educator teaching at a regional university, over the last six years I have attempted to pursue the development of a more Indigenous-inclusive curricula and thus contribute to increasing Indigenous graduates from our degree programmes. This article documents some of my actions to rectify gaps in my own non-Indigenous knowledge base as a reflective learner under Indigenous supervision within the academy and in the community. Action to advance the development of accurate, useful curriculum and teaching practices respectful of Indigenous knowledges is recommended.